MRCS Part B OSCE : anatomy - Lynch, Jeremy; Shelmerdine, Susan (JP Medical, 2013)
MRCS PART B OSCE: ANATOMY is unique in focussing solely on providing the knowledge necessary to pass one of the toughest exam components facing surgical trainees.